Aspectos espaciais dos acidentes escorpiônicos em Uberlândia, Minas Gerais - Faria, Marcelo Araújo de (2021)
The use of analytical tools based in Exploratory Spatial Data Analysis can be the basis for the clear understanding of the behavior of an illness within the population of a specific area. Controlling and mapping of these events become an important key factor in the construction of investigative approaches for the environmental health. Thus, specific questions can be answered, such as, “Does the occurrence of scorpion stings have any relationship with rainfall rates?”. The present research proposed to carry out critical analyzes on academic production in studies of Exploratory Analysis of Spatial Data in cases of scorpionism and, considering the gap in scorpionism research, presented a study on the behavior of scorpionism cases in the urban area of municipality of Uberlândia/MG, between 2015 and the first quarter of 2020. The critical analysis of scientific articles published between 2010 and 2020 found that few studies on scorpionism used Exploratory Spatial Data Analysis methodologies. The research carried out by the present work proposes to stimulate the discussion about the benefits for the formation of public health policies. From the spatial autocorrelation method involving two variables - places where scorpion stings occurred and places where scorpion control activities took place - it was possible to identify the control of the scorpionism outbreak that occurred during 2016, with a reduction in cases in the year 2018. Another result that the work identified were census sectors with high records of accidents and with low records of preventive activities against the proliferation of scorpions, which indicated census sectors outliers on cases of scorpionism in Uberlândia. Considering the benefits of using a methodology based on exploratory analysis of spatial data, this research exposes and discusses the advantages of the techniques used to control cases of scorpionism.